Determination of Nasab Validation of Children Born Outside a Legal Marriage (Study Analysis of the Religious Court Decision Number: 115/PDT.P/2021/PA. Bjb) - Herianto; Sahmiar Pulungan (Dinasti Research, 2025)
The purpose of this study is to briefly explore the factors considered by judges in deciding the offspring status of children born from legal marriages and its legal impact, especially for unregistered children. This research is focused on analyzing regulations related to literature or secondary sources, utilizing a qualitative approach and normative legal methodology. The methods used in this research include a statute-based approach and a case-based approach. The research results show that:1) The judge in his decision rejected the plaintiff's request to affirm the child's relationship with his father. 2) The legal impact on children and women in a siri marriage according to the Overview of Islamic Law is as follows: For the child, it is difficult to obtain a birth certificate because his birth is constrained by administration at the civil registry office. In contrast, the wife's status as a legal spouse is not recognized by state law.